ACToday Columbia World Project adopts and scaled out agricultural climate service innovations in Bangladesh, Colombia, Guatemala and Ethiopia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The ACToday Columbia World Project adopted climate information tools and innovations in its efforts to help target countries advance SDG-2: ending hunger, through improved climate services and risk management. The online climate information "Maproom" tools, based on high-quality gridded meteorological data, were developed earlier by CCAFS and IRI to meet agricultural decision-making needs. As a result, localized climate information and analyses are now available to the 30 million agricultural work force of Bangladesh, Colombia and Guatemala.